Can brief alcohol interventions in general hospital inpatients improve mental and general health over 2 years? Results from a randomized controlled trial. Issue 10 (4th September 2018) - Freyer-Adam, Jennis; Baumann, Sophie; Haberecht, Katja; Bischof, Gallus; Meyer, Christian; Rumpf, Hans-Jürgen; John, Ulrich; Gaertner, Beate
Abstract: Background: Little is known about the impact of brief alcohol interventions on mental and general health. The aim was to investigate whether brief interventions for general hospital inpatients with at-risk drinking can improve mental and general health over 2 years; and whether effects are dependent on how they are delivered: in-person or through computer-generated feedback letters (CO). Methods: Three-arm randomized controlled trial with 6-, 12-, 18-, and 24-month follow-ups. Data were collected on 13 general hospital wards from four medical departments (internal medicine, surgical medicine, trauma surgery, and ear-nose-throat) of one university hospital in northeastern rural Germany. A consecutive sample of 961 18- to 64-year-old general hospital inpatients with at-risk alcohol use was recruited through systematic screening. Inpatients with particularly severe alcohol problems were excluded. Participants were allocated to: in-person counseling (PE), CO, and assessment only (AO). PE and CO included three contacts: on the ward, 1, and 3 months later. Mental and general health were assessed using the five-item mental health inventory (0–100) and a one-item general health measure (0, poor – 4, excellent). Results: Latent growth models including all participants revealed: after 24 months and in contrast to AO, mental and general health were improved in PE (change in mean difference, Δ M mental = 5.13, p = 0.002, Cohen's d = 0.51; Δ M general = 0.20, p = 0.005, d = 0.71) and CO (Δ M mental = 6.98, p < 0.001, d = 0.69; Δ M general = 0.24, p = 0.001, d = 0.86). PE and CO did not differ significantly. Conclusions: Beyond drinking reduction, PE and CO can improve general hospital inpatients' self-reported mental and general health over 2 years.